Questioning Anthropocentrism in Christianity: Is the Book of Job in Line with the Principles of Environmental Ethics? - Turza, Zoran (Studia Ecologiae et Bioethicae, 2026)
In 1967, historian Lynn White argued that religions, particularly Christianity, have significantly contributed to environmental degradation due to their inherently anthropocentric worldview. However, whether Christianity is fundamentally anthropocentric remains a topic of active scholarly debate. The central thesis is that Christianity should be understood as a religious system based on ethical principles that transcend anthropocentrism. Rather than being identified with anthropocentrism, Christianity establishes its ethical norms by understanding the interconnectedness of all living beings on Earth. This interconnectedness is reflected in God’s invitation to people and all creation for communion with Him. In this context, the understanding of humanity in Christianity is rooted in the recognition that humans exist in relationship with God, their neighbours, and the wider natural world. This thesis is tested by investigating whether the Old Testament’s “Book of Job” advocates anthropocentrism. More specifically, the article analyses how this book aligns with two foundational principles of environmental ethics: the good of being and the concept of inherent worth. The results indicate that the Book of Job largely adheres to the principles of environmental ethics, suggesting that the criticisms typically aimed at anthropocentrism cannot be applied to Christianity. The analysis of The Book of Job affirms that Christianity transcends anthropocentrism by presenting a view of humanity that cannot be understood without considering the relationships established by God between humans, their fellows and all of creation.